The relationship of recurrent aphthous stomatitis and Helicobacter pylori, cytokine gene polymorphism and cobalamin - Yakar, Tolga; Serin, Ender; Coşar, Arif Mansur; Arslan Taş, Didem; Ataç, Fatma Belgin (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: The aim of the present study was to investigate whether Helicobacter pylori causes or triggers recurrent aphthous stomatitis (RAS) through cytokine gene polymorphism and/or cobalamin deficiency. Materials and Methods: Thirty-six patients with RAS and 130 patients without RAS were genotyped for IL-1β (−511C/T) and IL-6 (−174G/C) and evaluated for H. pylori infection and serum cobalamin level. Results: The patient groups according to RAS had similar rates of H. pylori gastritis and interleukin genotypes/alleles, and there was a non-significant difference between serum cobalamin levels (p>0.05). RAS patients with H. pylori gastritis showed a higher frequency (51.9%) of GC IL-6 genotype than RAS patients without H. pylori gastritis (11.1%) (p=0.036). Non-GG genotype and C allele were increased in patients without RAS and with H. pylori gastritis (p<0.05). Patients with H. pylori gastritis showed a lower value of serum cobalamin without statistical significance, although this difference was more prominent in RAS patients (p=0.07). Conclusion: The carriage of the C allele of IL-6 may lead a susceptibility to chronic gastric inflammation after contamination with H. pylori. If H. pylori infection is justified as a predisposing factor for RAS and its severity by further studies, we can speculate that subjects with genetic susceptibility to this infection may benefit from H. pylori eradication treatment with respect to RAS.